The Anthropology of Plastic Waste: A Study of Community Adaptation and Resistance to Marine Pollution in a North Javanese Coastal Village - Roya Zahir; Safiullah Aziz; Zara Ali; Restu Auliani (Yayasan Adra Karima Hubbi, 2025)
Background. Plastic pollution has become a defining environmental challenge for coastal communities in Southeast Asia, particularly in North Java, where rapid urbanization, industrial activities, and waste mismanagement exacerbate marine degradation. Local communities are not merely passive victims of this ecological crisis; they actively navigate, reinterpret, and resist the social and environmental impacts of plastic waste. Purpose. This study aims to investigate how a North Javanese coastal village adapts to and challenges marine pollution through cultural practices, social organization, and collective environmental action. Method. An ethnographic research design was employed, integrating participant observation, in-depth interviews, household surveys, and environmental field notes to generate a multi-layered understanding of community responses. Results. The findings reveal three central patterns: first, adaptive behaviors emerge through pragmatic strategies such as waste repurposing and informal recycling networks; second, environmental degradation reshapes local cosmologies and cultural narratives surrounding cleanliness, morality, and human–nature relationships; third, forms of resistance manifest through community-led cleanups, youth environmental activism, and negotiations with local authorities and industries contributing to pollution. Conclusion. The study concludes that community adaptation and resistance are driven by intertwined ecological, economic, and cultural dynamics, illustrating that environmental crises are socially mediated phenomena requiring context-sensitive interventions.